Zakat Management Model by Imuem Meunasah Based on Baitul Mal Gampong in Aceh - Taufiq, Taufiq; Ananda, Faisar; Suparmin, Sudirman (IKONOMIKA, 2022)
Zakat management institutions in Aceh are different from other provinces. It was stated in Law no. 11 of 2006 that it concern Baitul Mal and Law No. 10 of 2007 that zakat management institutions reach the village level, Baitul Mal Gampong led by Imuem Meunasah as a customary institution that oversees the implementation of Islamic law. The establishment of zakat institutions at the village level in Aceh is to explore and manage zakat potential followed by good management because the potential of zakat circulates at the village level. Likewise, Imuem Meunasah was established as one of the traditional institutions to lead the zakat institution, Baitul Mal Gampong, to build public trust in the zakat institution. In reality, zakat management by zakat institutions at the village level in Aceh led by Imuem Meunasah has not had an impact according to the objectives, both in terms of collection and distribution. This study aims to find out the problems that occur and get strategic solutions, both internally and externally, to the problem of zakat management by Imuem Meunasah at zakat institutions at the village level. The research methodology is descriptive qualitative using the ANP analysis tool with seven respondents. There are two problems in the management of zakat by Imuem Meunasah as the head of Baitul Mal Gampong. The main problem is the internal aspect as well as related to strategic solutions. The internal problems are human resources with a rater agreement value of 34, 93%, Synergy with a rater agreement r value of 28,39%, and Socialization with a rater agreement value of r 36,66%. The solutions in this study are related to Duty and area, Selective, and Out of the Box. The existence of Imuem Meunasah as the Chairman of Baitul Mal Gampong must still be maintained. Meanwhile, the socialization aspect must be transparent, creative and innovative.